Expandiendo nuestro conocimiento conceptual y metodologico sobre el rol de arboles y bosques en la subsistencia rural - Luckert, M.K.; Campbell, Bruce M. (Nordan-Comunidad, 2002)
Estimates of forest values may enable us to inform policy makers, donor agencies, and local decision makers who are attempting to plan and implement interventions that improve livelihoods. However, it needs to link these values with patterns of behaviour; and link the patterns of behaviour with changes in livelihoods. Whether or not behavioural change occurs depends on a number of factors; these include property rights, social differentiation, time, risk perceptions, and whether values are considered in “partial” or “general” contexts. Discussion of these factors indicate that the estimation of values themselves are not as important as their interpretations within specific contexts. This article suggests that the conceptual models of people and their resources, in terms of livelihoods, need to be expanded. It also suggests that it needs to consider relevant systems beyond socio-economic variables. It also needs to expand the methodological boundaries; thus, for example, valuation approaches need to be interfaced with GIS, systems modelling. The infancy of using applied economics tools in developing country settings is evident throughout this book. Indeed, many of the tools are so new, and complex, that their use is still sometimes hotly debated. Nonetheless, the examples presented in this book show that great strides have been made, largely through benefits of inter-disciplinary work. Economics experts, specialising in valuation methods and property rights, have been working with sociologists, anthropologists and ecologists to attempt to address the complexities inherent in introducing human dimensions into research to inform development projects and policies.